CONSTRUCTIVE SOLUTION OF A TUNNEL UNDER THE EXISTING HIGHWAY - Timchenko, R. A.; Krishko, D. A.; Macyshin, S. О. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Urban underground structures (shallow tunnels), which are usually built in conditions of urban area with heavy traffic, are considered. It was clarified that the reinforced concrete lining are performed of concrete, reinforced concrete, natural and artificial stones in most cases. The types of tunnels road cutting are given. The geometrical dimensions and characteristics of using materials in the construction of tunnels are given. It was established that the existing methods of tunnel construction do not allow to solve the problem in cramped conditions and intense traffic. The new constructive solution of the transverse tunnel under the existing highway was proposed. It is found that the proposed design of the transverse tunnel may be performed in cramped urban environments with the use of modern technological equipment and the proposed method of tunnel meets the requirements of strength, reliability, durability.
Keywords: cross-tunnel; tunnel lining; installation of horizontal directional drilling